Fifty-Five Years of Pediatric Endocrinology and 50 Years of the Department of Pediatric Endocrinology, Diabetes and Metabolic Diseases in Slovenia - BATTELINO, Tadej (Zdr Varst, 2015)
Paediatric endocrinology started its independent development early in the general development of this specialty, with a strong focus on research and clinical excellence. Slovenian paediatric endocrinology was an integral part of the European paediatric endocrinology from its beginnings and a founding member of the first ‘International Study Group for Diabetes in Children and Adolescents’. After the pioneering work of Prof. Lev Matajc, Prof. Ciril Kržišnik firmly integrated the Department of Pediatric Endocrinology, Diabetes and Metabolic Diseases at the University Children’s Hospital in Ljubljana in the international scientific community. In the last decade, the department participates in cutting-edge research and provides clinical services at highest international standards.